Avaliação tomográfica da reabsorção radicular em molares mesializados em área edêntula - Pimenta Junior, Bolivar (2018)
Introduction: The purpose of this retrospective study was to quantify the root resorption of the mesial surface of the protraction molar roots with anchorage in mini-implants. Methods: A sample of 17 maxilar and mandibular molars from 11 patients with a mean age of 37.5 years who had Cone Bean Computed Tomography (CBCT) before treatment (T1) and after 4 mm (T2), with an average time of 23,5 months. The magnitudes of the resorptions were measured in the sagittal sections of the tomography, cervical, mid and apical thirds by the OnDemand software, with reference to the cementoenamel junction (CEJ), calculated by the difference in height and depth of resorption in mm, between T1 and T2 in the two examinations of the protractioned molars. Statistical analysis was performed using the paired t test. To verify if there was a statistically significant resorption, the monocaudal t-test was used, adopting the significance level of 5%. Pearson's coefficient was used to verify the correlation between age and time of treatment with the amount of resorption. Results: In the middle and apical thirds there was resorption, but statistically significant only in the middle third. The correlation between age and time of treatment with the resorption was not statistically significant. Conclusion: Although the results showed significant statistical differences in the middle third, there was root resorption on the mesial surface in 17.6% of the teeth, but it is not clinically significant, therefore, providing a treatment with minimum biological cost.